Improvements and limitation of soy protein‐based adhesive: A review - Sofie Zarina, Lamaming; Junidah, Lamaming; Nurul Fazita, Mohammad Rawi; Rokiah, Hashim; Mohamad Haafiz, Mohamad Kassim; Mohd Hazwan, Hussin; Yazmin, Bustami; Othman, Sulaiman; Mohd Hazim, Mohamad Amini; Salim, Hiziroglu (Society of Plastics Engineers., 2021)
Soy protein is known for its eco-friendly, sustainable, and biodegradable qualities that are likely used as raw material in producing bioadhesive. However, soy protein-based adhesive are lacking in terms of adhesive strength and water-resistance compared to commercial formaldehyde-based adhesives such as phenol and urea-formaldehyde resin. Therefore, continuous research has been done to improve adhesive performance. This can be done via physical or modification methods, including the usage of cross-linking agents, structural modification, enzymatic modification, and the addition of additives. This review will cover these modification methods that give significant enhancement to the water-resistance and adhesive strength of soy protein-based adhesives.